Innovation in Reactive Agility Test Measurement of Basketball Performance: Content Validity and Inter-Rater Reliability - SeptianaWijayanti, Tomoliyus, IrmantaraSubagio,Fauzi, (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2021)
Basketball performances can be maximized if the athletes have good reactive agility abilities. So far, assessment using the reactive agility test could only be applied to volleyball, table tennis, rugby, and football, while basketball is still using the general agility test. The reactive agility itself is defined as the body’s ability to change direction at high speed after receiving a stimulus. To assess the results of reactive basketball agility, a valid and reliable measuring instrument was needed. Therefore, this study aimed to test the content validity and inter-rater reliability of the basketball agility reactive test instruments that had been made.The methods used in this research were qualitative and quantitative, with several documents and seven experts as the participants. The first stage of the study was a qualitative method in the form of literature reviews. The second stage was data collection using the Delphi technique. A rating scale that ranged from 1 to 4 was applied in this study. The data analysis formula for this study was Aiken’s, which aimed to test the content validity of the basketball performance reactive test instrument. Meanwhile, to test the inter-rater reliability, the study applied Alpha Cronbach’s formula.This study produced a reactive agility test instrument for basketball performance with Aiken’s coefficient of each aspect above 0.76 and reliability of 0.944. Therefore, it can be concluded that all aspects of the test instrument were valid, and the instrument has remarkable stability